Phenotypic identification of indigenous fungi and lactic acid bacteria isolated from ’gatot’ an Indonesian fermented food - ASTRIANI ASTRIANI; NURUD DINIYAH; JAY JAYUS; NURHAYATI NURHAYATI (Biodiversitas Journal of Biological Diversity, 2018)
Astriani A, Diniyah N, Jayus J, Nurhayati N. 2018. Phenotypic identification of indigenous fungi and lactic acid bacteria isolated from ’gatot’ an Indonesian fermented food. Biodiversitas 19: 947-954. As a traditional Indonesian food made from cassava, ‘gatot' has special attracted characters of black appearance and chewy texture, mainly as a result of certain fungi and lactic acid bacteria (LAB) during the spontaneous fermentation. However, many producers were failed to gain these typical properties since much unwanted microbial strain often appears during the spontaneous fermentation. Therefore, this study was conducted to isolate and identify the indigenous fungi and LAB which predominantly contributed in fermentation of cassava during ‘gatot’ production. Fungi and LAB were isolated from conventionally made of the ‘gatot’ followed by the phenotypic identification of the isolates based on the morphological and physiological properties. The fungi isolates were morphologically distinguished by the type of mycelia, the shape, and color of the sporangium, while the LAB strains were identified by the type of cell and colony form. In addition, the physiological behavior of the LAB isolates was characterized by their typical growth temperature, its catalase activity and its fermentation profile using BBL crystal kit test. The predominant fungi isolates were identified as Botryodiplodia theobromae, Rhizopus oligosporus, Trichoderma sp. and Aspergillus niger. B. theobromae had greyish white to black color of mycelia when it mature. R. oligosporus had globose sporangium and blackish grey color of the mature mycelia. Trichoderma sp. had green color of the mature sporangium and mycelia. A. niger had yellow color of the mycelia and black color of sporangium. Meanwhile, the indigenous LAB was majority identified as Lactobacillus manihotivorans, Bacillus licheniformis, Brevibacillus brevis and Lactobacillus fermentum. Those bacteria were gram-positive, rods shape, catalase-negative and grew optimally at 37oC. The LAB also arise frequently in many spontaneously fermented food. B. theobromae, R. oligosporus, L. manihotivorans, and L. fermentum were potential and non-pathogenic microbial, which can be used as a starter culture to produce ‘gatot’ under controlled fermentation process.